Clinical Profile and Outcome of Dengue Fever in Pediatric Patients: A Hospital-Based Study - Saira Jahangir, Syed Musaddiq Zanjani, Syed Muhammad Sheharyar Zanjani, Sughra Wahid, Maham Amin, Sobia Nawaz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dengue fever remains a major public health concern in Pakistan, with a rising burden among pediatric populations. Early identification of warning signs and laboratory predictors is essential to prevent progression to severe disease and related complications. Objective To assess the clinical characteristics, severity patterns, and outcomes of dengue fever in pediatric patients, and to identify factors associated with severe dengue. Methods This descriptive cross-sectional study was conducted at Mayo Hospital, Lahore from September 2021 to February 2022, included 265 laboratory-confirmed pediatric dengue patients aged 1 month to 14 years. Clinical features, WHO 2009 dengue classification, laboratory parameters, complications, and outcomes were documented. Results: Among 265 children, 60.4% were male, with a mean age of 7.1 ± 3.8 years. Dengue without warning signs (43.0%) and dengue with warning signs (42.6%) were the most common categories, while 14.3% developed severe dengue. Severe dengue was significantly associated with thrombocytopenia (<50,000/mm³), raised hematocrit (>45%), hepatomegaly, and elevated ALT levels (p<0.001). Complications included hypotension (7.5%), bleeding (5.7%), and fluid overload (4.9%); 15% required ICU care. Mortality was low at 0.4%. Conclusion: Dengue fever in children presents with a wide clinical spectrum, and a subset progresses to severe disease. Key clinical and laboratory markers, particularly thrombocytopenia, elevated hematocrit, hepatomegaly, and transaminitis, serve as strong predictors of severe dengue. Early recognition and adherence to WHO management protocols play a critical role in reducing morbidity and mortality. Keywords: Dengue fever, Pediatrics, Severe dengue, Thrombocytopenia, Hematocrit, Clinical outcomes.